Hydrophilic polyisophthalamides containing poly(ethylene oxide) side chains: Synthesis, characterization, and physical properties. Issue 4 (27th November 2012) - Carretero, Paula; Molina, Serena; Sandín, Ricardo; Rodríguez‐Hernández, Juan; Lozano, Angel E.; Abajo, Javier de
Abstract: Novel polyisophthalamides containing pendent poly(ethylene oxide) (PEO) sequences were prepared by grafting PEO onto poly(5‐hydroxy‐isophthalamide)s (HO‐PIPAs). First, an optimized method of synthesis was applied to prepare HO‐PIPAs, following the rules of the direct polyamidation reaction promoted by triphenyl phosphite and catalyzed by pyridine. Next, the modification of HO‐PIPAs was performed by a nucleophilic substitution reaction with chlorine‐terminated PEO monomethyl ether of average molecular weight 100, 550, and 1000 g/mol. The modification (grafting) reaction was optimized to assure virtually 100% yield. Polymers behaved as graft or brush‐like copolymers of polyisophthalamide (PIPA) and PEO, covering a wide range of ratios of PIPA/PEO. Physical properties, such as solubility, glass transition temperature, and thermal resistance were determined. Special attention was paid to the affinity of the novel copolymers for water. It was realized that with a high content of PEO, the materials could absorb water in amounts exceeding their own weight. Gravimetric methods and water contact angle measurements were used to quantify the hydrophilicity of the current PIPA‐ g ‐PEO copolymers. © 2012 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem, 2013 Abstract : Polyisophthalamides with side chains of polyethylene oxide (PEO) were prepared by incorporating PEO sequences onto poly(5‐hydroxy‐isophthalamide)s. The polymers behaved as graft copolymers of polyisophthalamide (PIPA) and PEO, covering a wide range of ratios of PIPA/PEO. For high contents of PEO, the materials could absorb water in high amounts and they tended to micellize in polar solvents. Gravimetric methods and water contact angle measurements were used to quantify the hydrophilicity of the current PEO‐modified polyisophthalamides.